Optimisation of glucose templated silica for oil-water separation / Nurul Atiqah Mustaffa, Nur Hafizah Abd Hamid and Siti Nurehan Abd Jalil - Mustaffa, Nurul Atiqah; Abd Hamid, Nur Hafizah; Abd Jalil, Siti Nurehan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
In this study, glucose is used as a template to manufacture microporosity in silica. Based on this objective, five different molar ratios of glucose (0%, 10%, 20%, 30% and 50%) were used for this experiment to maximise its affinity to adsorb oil droplets. The sample has been characterized using thermogravimetric analysis (TGA), Nitrogen Adsorption and UltravioletVisible (UV-Vis) Spectroscopy. The adsorption of oil was tested in 1000 ppm oil-water emulsion in order to determine the performance of the templated silica. TGA analysisshowed that 550 ̊C is a suitable temperature for material calcination for all the samples. N2 adsorption showed the glucose templated silica (50%) had limited porosity, with a low surface area of 2 m2 /g. This is much lower than non-templated silica which was mesoporous, with an average pore diameter of 2.6 nm and a surface area of 272 m2 /g. Interestingly, despite the low porosity of the templated silica, high oil-water separations were achieved. This shows that glucose-templated silica is a promising material for oil-water separations